Biosphere Reserve Concept Implementation for Creating Sustainability - Y. Purwanto; Hari Nugroho; Anang Setiawan Achmadi; Esti Munawaroh (The Ethnobiological Society of Indonesia, 2020)
The main priority of UNESCO MAB program is to emphasize the implementation of biosphere reserve concept for achieving sustainable development. Biosphere reserve is a concept of site management to harmonize the needs for conservation of both land and coastal ecosystem with the need for economic development in the basis of research on the utilization of natural resources, including cultural resources recognized by UNESCO MAB Program in order to promote a balanced relationship between human and the nature. Principally, the concept of biosfer reserve is applied to bring the conservation of biological diversity into line with sustainable development for achieving a balanced relationship between human and the nature. The advantage of applying the biosphere reserve concept lays on the excellent combination of its three functions, namely: (1) The function associated with conservation of biological resources, ecosystems, and cultural diversity; (2) The function associated with development that supports and enriches sustainable economic development through an ecologicaly and culturally wise approach; and (3) The function associated with provision of logistics supports for various activities related with conservation and sustainable development, in a local, regional, national, or global context, including research, education, training, and monitoring. In implementing those three functions integratively, a zonation approach is applied, in which the site of biosphere reserve is devided into three different areas with specific functions and roles: (1) The core area: It is the area for conservation and it must have a firm, long-term legal protection for preserving the biodiversity, monitoring the undisturbed ecosystems or undertaking non-destructive research, and other “passive” activities such as education and training and ecosystem services; (2) The buffer zone: It is the area encircling or adjoining the core area that is determined to provide protection to the core area against the negative impacts of human activities; and (3) The transition area: The transition area. It is typically the largest part of the biosphere reserve area fuctioning to develope cooperation with local communities. It is established side by side with the buffer zone and this area is a place to develope models for sustainable development and develop an appropriate management of natural resources for the area. Biosphere reserves are used as a place to test and build a sustainable way of life through integrated programs of natural resources management and biodiversity conservation, with the objective to contribute in reducing poverty and increasing the living standard, especially of rural communities. In addition, the implementation of the biosphere reserve concept is also aimed to help reducing the loss of biodiversity, facilitating scientific development and bulding the capacity in the context of providing services neccessary for ecological sustainability.